Menavigasi Mimpi dalam Pelayanan Pastoral: Sebuah Pendekatan Biblika dan Teologis - Illu, Jonidius; Keluanan, Yane Henderina; Nome, Nehemia; Hia, Yeremia (STT Pelita Dunia, 2025)
This article aims to provide a comprehensive and theological understanding of the phenomenon of dreams within the context of pastoral ministry, particularly from a faith perspective grounded in the authority of Scripture. The author seeks to examine how dreams are portrayed and utilized in biblical narratives as a means of divine revelation, and how these principles can be applied wisely in pastoral care. Additionally, this study intends to construct a biblically and theologically sound framework for evaluating dream experiences, so that church leaders may guide congregants responsibly and avoid misleading or speculative interpretations. Using a qualitative method and a biblical-theological approach, this study analyzes key texts such as Genesis 28, Daniel 2, and Matthew 1, and compares them with theological principles concerning revelation and the authority of Scripture. Theories of general and special revelation are employed to distinguish between dreams as a medium of divine communication and those originating from human psychological processes. The main findings indicate that while dreams may serve as a channel of revelation, their interpretation must be tested against Scripture and accompanied by pastoral wisdom. Therefore, this article offers a theologically grounded and pastorally responsible framework for church leaders to navigate the phenomenon of dreams without falling into spiritual speculation, subjective experience, or cultural syncretism.